Asymmetric Effect of Real Exchange Rates on Import Expenditures - Kanca, Osman Cenk (ETIKONOMI, 2025)
Research Originality: This study contributes to the literature by investigating the asymmetric effect of the real exchange rate on real import expenditures in Turkey.Research Objectives: This study aims to investigate the short—and long-run symmetric/asymmetric effects of the exchange rate on import expenditures in the Turkish economy.Research Methods: The study utilized both a linear Distributed Lag Autoregressive (ARDL) bounds testing approach and a nonlinear ARDL (NARDL) model, using a dataset from 1980 to 2022.Empirical Result: The findings indicate that the real exchange rate has asymmetric effects on real import expenditures in the short run. The error correction model results reveal that short-run shocks among variables will lose their impact in the long run, and the co-movement of variables will correct itself in approximately 3 and 1.5 years.Implications: These results shed light on policymakers shaping Turkey’s import regime. In addition, adopting policies that provide macroeconomic balance based on real exchange rates is considered a crucial factor in reducing external dependency and eliminating Turkey’s foreign trade deficits. JEL Classification: C40, E00, F31How to Cite:Kanca, O. C. (2025). Asymmetric Effect of Real Exchange Rates on Import Expenditures. Etikonomi, 24(1), 135 – 154. https://doi.org/10.15408/etk.v24i1.38967